Analysis of education for sustainable development research hotspots based on vosviewer and citespace - Ou, Wanzhen; Mohd Shariff, Shaliza; Mohd Tajuddin, Rosita (Journal of Islamic, Social, Economics and Development, 2025)
Education for sustainable development (ESD) is the key to the realisation of a sustainable future based on the symbiosis of man and the earth. Although weak ESD based on technocentric has to a certain extent popularised knowledge about the environment and sustainable development and raised people's understanding and awareness of sustainable development, it has failed to fully realise the transformative potential of ESD in promoting social, economic, environmental, cultural and educational change towards a sustainable development path. The purpose of this study is to understand the hotspots and frontiers of ESD research. Methods: Using VOSviewer and CiteSpace software, 1895 English articles on ESD in the Web of Science Core Collection from 2000 to 2023 were analysed for bibliometrics such as country, research institution, author, and keywords. As a result, Germany is the country with the largest number of publications. KARLSTAD UNIV was the most published institution and Niklas Gericke was the most published and cited author. Among the 30 most frequent keywords, the keywords "sustainable development", "education", "environmental education", "higher education" and "students" are broader. While the keywords "knowledge", "competences", "attitudes", " behaviour", "impact", "climate change", "policy", "science", "teachers", "education", "education", "education", "education", "education". "science", "teachers" and "curriculum" reflect some of the current hot topics in the field of ESD. In conclusion, based on the keyword analysis, it can be concluded that the current hotspots of research on ESD are mainly interdisciplinary education research, teacher and policy development research, and students' knowledge, attitudes, and behaviour toward sustainable development.